Highly specific and sensitive non-radioactive molecular identification of Phytophthora cinnamomi - Coelho, A C; Cravador, A; Bollen, A (Mycological Research, 1997)
In response to the need for a faster, more reliable method for identifying Phytophthora cinnamomi in cork oak soils in Portugal, a simple, fast, sensitive molecular identi®cation method is described. It is based on a colorimetric assay which involves an oligonucleotide capture probe covalently immobilised on microtitration wells, a multi-biotinylated oligonucleotide detection probe and the PCR-ampli®ed target DNA. The target DNA is a 349 bp DNA fragment partially covering the 3«-translated and 3«- untranslated regions of the cinnamomin gene. When the speci®city of the PCR reaction was evaluated in vitro using isolates of P. cinnamomi and eight other Phytophthora species, including the related P. cambivora, it was speci®c to P. cinnamomi. When 30 isolates of P. cinnamomi from oak roots in southern Portugal were assayed, 26 gave a strong positive response. The assay has a sensitivity of about 2±5 genome equivalents of P. cinnamomi. The reason for the negative response of four isolates remains unclear.
Keywords: Cork oak soils; Iidentification method; phytophthora cinnamomi